Human Immunodeficiency Virus Infection and Host Defense in the Lungs - Charles, Tysheena P.; Shellito, Judd E. (Seminars in Respiratory and Critical Care Medicine, 2016)
Immunosuppression associated with human immunodeficiency virus (HIV) infection impacts all components of host defense against pulmonary infection. Cells within the lung have altered immune function and are important reservoirs for HIV infection. The host immune response to infected lung cells further compromises responses to a secondary pathogenic insult. In the upper respiratory tract, mucociliary function is impaired and there are decreased levels of salivary immunoglobulin A. Host defenses in the lower respiratory tract are controlled by alveolar macrophages, lymphocytes, and polymorphonuclear leukocytes. As HIV infection progresses, lung CD4 T cells are reduced in number causing a lack of activation signals from CD4 T cells and impaired defense by macrophages. CD8 T cells, on the other hand, are increased in number and cause lymphocytic alveolitis. Specific antibody responses by B-lymphocytes are decreased and opsonization of microorganisms is impaired. These observed defects in host defense of the respiratory tract explain the susceptibility of HIV-infected persons for oropharyngeal candidiasis, bacterial pneumonia, Pneumocystis pneumonia, and other opportunistic infections.
Keywords: HIV infections; host defense against infection; T-lymphocytes; B-lymphocytes; lung infections